2012
DOI: 10.1021/nl300009z
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Ferroelectric-Film Solar Cells with an n-type Cu2O Cathode Buffer Layer

Abstract: Because of the existence of interface Schottky barriers and depolarization electric field, ferroelectric films sandwiched between top and bottom electrodes are strongly expected to be used as a new kind of solar cells. However, the photocurrent with a typical order of μA/cm(2) is too low to be practical. Here we demonstrate that the insertion of an n-type cuprous oxide (Cu(2)O) layer between the Pb(Zr,Ti)O(3) (PZT) film and the cathode Pt contact in a ITO/PZT/Pt cell leads to the short-circuit photocurrent inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
159
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(162 citation statements)
references
References 35 publications
3
159
0
Order By: Relevance
“…Photovoltaic effect has been reported in many ferroelectric materials (such as BiFeO 3 , Pb(Zr,Ti)O 3 , and Bi 2 FeCrO 6 ) with best efficiency of 8.1% for ferroelectric solar cells based on Bi 2 FeCrO 6 [20][21][22][23][24][25][26][27][28][29]. These ferroelectric solar cells have been proposed to utilize the polarization electric field to drive the charge separation and transport.…”
Section: Introductionmentioning
confidence: 99%
“…Photovoltaic effect has been reported in many ferroelectric materials (such as BiFeO 3 , Pb(Zr,Ti)O 3 , and Bi 2 FeCrO 6 ) with best efficiency of 8.1% for ferroelectric solar cells based on Bi 2 FeCrO 6 [20][21][22][23][24][25][26][27][28][29]. These ferroelectric solar cells have been proposed to utilize the polarization electric field to drive the charge separation and transport.…”
Section: Introductionmentioning
confidence: 99%
“…Many ferroelectric materials with relatively high Curie temperature have been demonstrated; these materials can be used in solar cells because they can retain their ferroelectric properties even at practically high temperatures associated with the operation of solar cells. Significant research has been performed on the photovoltaic characteristics of BTO [20,21], lead zirconate titanate (PbZrxTi1−xO3, PZT) [22][23][24], bismuth titanate (Bi4Ti3O12) [25], potassium sodium niobate (K0.5Na0.5NbO3, KNN) [26,27], and BFO [21,28,29].…”
Section: Advances and Open Issuesmentioning
confidence: 99%
“…In light of the above-mentioned limitations, the conversion efficiency of conventional simple MFM and MSM structures cannot meet the requirements imposed by practical applications. For a simple ITO/PZT/Pt structure, the device consists of two back-to-back Schottky diodes, and the work function of the Pt electrode is high (5.6 eV) so that most of the electronics cannot cross into the interface Schottky barrier of the Pt electrode, and it is difficult to increase the current [22]. When studying the photovoltaic effect in ITO/ZnO/BFO/Pt heterostructures, Fan et al [67] discovered that the ZnO/BFO interface can form an n + -n junction.…”
Section: Combination With Various Materialsmentioning
confidence: 99%
“…Recently, more studies have shown that the value of the above-band gap photovoltage of ferroelectric BiFeO 3 can be tuned by varying the number of nanometre scale domain walls with alternating polarity, and additionally, by varying the applied electrical field [183]. However, the efficiency of such devices based on ferroelectric materials such as BiFeO 3 and Pb(Zr,Ti)O 3 (PZT) remains very low due to the low fill factor and Jsc [184][185][186] PV cells using KNbO 3 , another perovskite ferroelectric material, as the absorber have been reported [53].…”
Section: Ferro Electric Photovoltaicsmentioning
confidence: 99%